Response of oocytes of the immature catfish (Clarias Macrocephalus gunther) to hyphophysical hormones, placental gonadotropin, adrenocortical steroids and steroid precursors an in vitro study. - Herreran Annabelle Aliga (1975)
The in vitro effect of hypophysical hormones, placental gonadotropin, andrenocorticosteroids and steroid precursor on the oocytes of the immature catfish (Clarias macrocephalus Gunther) was determined by culturing ovarian fragments in Eagle's minimal essential medium at 22+24oc for 1, 2, 3 days. The result suggest that under experimental conditions the hormones' effectiveness in promoting oocyte development in in the following order : desoxycorticosterone acetate, cortisome acetate, hydrocortisone, salmone gonadotropin, human chorionic gonadotropic, rat pituitary extract and progesterone. Ovine FSH was ineffective.
Thesis (Graduate, Master of Science (Zoology) ) - University of the Philippines System, April 1975.
Keywords: Catfish; Clarias macrocephalus Gunther